Exploring Well-being Influences on Mathematics Learning at University - Hamidiyah, Shafa Aulia; Erliana, Variza Wamer; Wahyunengsih, Wahyunengsih (Universitas Dehasen Bengkulu, 2025)
This study explores the influence of well-being on mathematics learning among university students. It addresses the limited research on how well-being affects mathematics learning in higher education. Data from 68 respondents were processed using quantitative methods; this study investigated the relationship between several aspects of well-being and mathematics learning. The results demonstrated that psychological health and Behavior significantly influence students' mathematical understanding. While subjective well-being, Emotion, and spiritual well-being showed less significant effects in this context. The study highlights the importance of backing students' emotional and mental well-being to enhance their learning in mathematics at the university level. It accentuates that academic programs should arrange these aspects to create a more effective learning environment.